Modeling and vulnerability of historical city centers in seismic areas : a case study in Lisbon - Ramos, Luís F. (2004)
Historical city buildings are an integral part of the built heritage to be preserved, and their safety is a primary requirement in seismic areas. Collapse of ancient masonry buildings due to seismic actions occur mostly due to overturning of the perimeter walls. This paper addresses the issue of seismic analysis and vulnerability of historical city centers, with a specific case study: the 18th century downtown part of Lisbon, Portugal. The finite element method was adopted for a number of different analyses, introducing non-linear behavior of the materials. From the analysis, the following issues have been addressed: (a) seismic vulnerability of this type of constructions; (b) influence of the group of buildings on the seismic behavior of the individual buildings that compose a single compound; and (c) methodology for action. It is believed that the conclusions obtained with respect to the seismic assessment of masonry buildings can be extrapolated for the wide variety of historical city centers.